Analisis Perbaikan Sistem Kerja pada Pembuatan Batu Bata - Mauluddin, Yusuf; Futra, Ricky Burnama (Institut Teknologi Garut, 2024)
This research discusses the analysis of work systems in brick making in small brick businesses. In this business, there are complaints from workers who often complain of pain in several parts of their body after they work. There are several complaints of musculoskeletal disorders experienced by workers, especially during the process of taking bricks to the drying area. Some of the work postures produced include a bent posture for quite a long time. The aim of the research is to improve the work system in brick making in terms of ergonomics related to work posture analysis, designing tools and improving work methods. The method used is a qualitative method guided by the Rapid Upper Assessment (RULA) posture analysis method. The results of the research show that the risk is high. After finding an unfavorable working posture, a tool is made that can change the work posture that is not suitable when working to a better one. The tool designed is making a drying mat in the form of an ergonomic rack.